Turbulence intencity of non-uniform open channel flow - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTACT: The turbulence intensities, u'/u. and v'/us for non-uniform open channel flow are investigated in detail and compared with the ones for uniform flow. It can be concluded that the profiles of turbulence intensities, u'lu. and v1/21., change with the pressure gradient. An acceleration of the mean flow is accompanied by a decrease (damping) of the turbulence intensities